Product Recycling Process of Old Stocks of Meharamae Motorcycle Parts: Basis for Proposed Marketing Strategy: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Meharamae Motorcycle parts shop was owned by the Geraldo Family. It was built a yearago. (2009) and MEHARAMAE comes from 4-person names: ME is Melda, Ha is Hazel, Rais Randy, and Mae is Razel Mae. Meharamae continued their shop, which from small hasnow grown and has three shops.The findings show that the majority of the respondents are male, ages 21-35; most aresingle and employed. Then, the study reveals an assessment of two groups of respondentson the product recycling process of Meharamae motorcycle parts in terms of generatedideas. Concept development and commercialization are "Strongly Agreed" The problemsencountered by the owner and employees of Meharamae Motorcycle Parts pertaining to theproduct recycling process are “Affordability of the stocks, price range, customer feedback,and the need for skilled technicians.”Based on the study, the researcher came up with the following discussions: 1.MEHARAMAE should give attention to marketing the business in ages 21-25 and 31-35because they already established their market in ages 21-35 years, in order to expand thescope of the business. 2. Meharamae Motorcycle parts need to be competitive in terms ofgenerated ideas, concept development, and commercialization. The recycling process needsto be disseminated understandably upon the ordering point. 3. Problems encounteredinclude affordability of the stocks, quality of the stocks, customer satisfaction, and the needfor skilled technicians. 4. The store crew needs to be open and politely answer questions orobjections referred by the customers about the Old Stocks and other matters. Provide apiece of information regarding the dissemination of the Old Stocks with the purpose ofraising the customer's awareness and avoiding certain objections.
Keywords: Business Administration